2019
DOI: 10.1111/dom.13840
|View full text |Cite
|
Sign up to set email alerts
|

Fixed versus flexible combination of GLP‐1 receptor agonists with basal insulin in type 2 diabetes: A retrospective multicentre comparative effectiveness study

Abstract: Background and Aims The combination of basal insulin (BI) and GLP‐1 receptor agonists (GLP‐1RAs) is a rational and effective therapy for patients with uncontrolled type 2 diabetes (T2D). We compared the effectiveness of fixed and flexible BI/GLP‐1RA combinations using routinely accumulated clinical data. Methods This was a retrospective, multicentre, real‐world study concerning T2D patients initiating a fixed or flexible BI/GLP‐1RA combination (NCT03959865). The primary endpoint was change in HbA1c. Secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
(51 reference statements)
3
18
0
Order By: Relevance
“…Observational studies, although unable to substitute for CVOTs, complement CVOT findings and can provide an estimate of true effectiveness in real‐world patients often not represented in CVOTs. Real‐world studies on the glycaemic and extra‐glycaemic effectiveness of GLP‐1RAs have confirmed findings from phase III RCTs, but there is still a paucity of cardiovascular real‐world studies . In a small study from the UK, the intensification of oral therapy by adding GLP‐1RAs was associated with a lower cardiovascular events rate than the intensification with insulin .…”
Section: Discussionmentioning
confidence: 94%
“…Observational studies, although unable to substitute for CVOTs, complement CVOT findings and can provide an estimate of true effectiveness in real‐world patients often not represented in CVOTs. Real‐world studies on the glycaemic and extra‐glycaemic effectiveness of GLP‐1RAs have confirmed findings from phase III RCTs, but there is still a paucity of cardiovascular real‐world studies . In a small study from the UK, the intensification of oral therapy by adding GLP‐1RAs was associated with a lower cardiovascular events rate than the intensification with insulin .…”
Section: Discussionmentioning
confidence: 94%
“…In this context, the present work, which is the second real-world study involving IDegLira, was carried out in an Italian context, with the aim to compare the effectiveness of fixed and flexible BI/GLP-1RA combinations using routinely accumulated clinical data. The results show that in specialist routine care, treatment with fixed or flexible BI/GLP-1RA combinations provide comparable improvement in glycemic control, with lower treatment costs with the fixed combination [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, missing data were handled with multiple imputation (MI). MI was performed as previously described 25 . Briefly a fully conditional specification (FCS) algorithm 26 was used to obtain 10 imputed datasets and including only covariates with less than 50% of missing values.…”
Section: Methodsmentioning
confidence: 99%